Mycobacterium bovis requires P27 (LprG) to arrest phagosome maturation and replicate within bovine macrophages - Vazquez, Cristina Lourdes; Bianco, María Veronica; Blanco, Federico Carlos; Forrellad, Marina Andrea; Gutierrez, Maximiliano Gabriel; Bigi, Fabiana (2017)
Mycobacterium bovis causes tuberculosis in a wide variety of mammals, with strong tropism for cattle and eventually humans. P27, also called LprG, is among the proteins involved in the mechanisms of the virulence and persistence of M. bovis and Mycobacterium tuberculosis. Here, we describe a novel function of P27 in the interaction of M. bovis with its natural host cell, the bovine macrophage. We found that a deletion in the p27-p55 operon impairs the replication of M. bovis in bovine macrophages. Importantly, we show for the first time that M. bovis arrests phagosome maturation in a process that depends on P27. This effect is P27 specific since complementation with wild-type p27 but not p55 fully restored the wild-type phenotype of the mutant strain; this indicates that P55 plays no important role during the early events of M. bovis infection. In addition, we also showed that the presence of P27 from M. smegmatis decreases the association of LAMP-3 with bead phagosomes, indicating that P27 itself blocks phagosome-lysosome fusion by modulating the traffic machinery in the cell host.